First, rewrite the equation as:
4x^2 - 9x + 0 = 0
We can now use the quadratic equation to solve this problem:
The quadratic formula states:
For color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0, the values of x which are the solutions to the equation are given by:
x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))
Substituting:
color(red)(4) for color(red)(a)
color(blue)(-9) for color(blue)(b)
color(green)(0) for color(green)(c) gives:
x = (-color(blue)((-9)) +- sqrt(color(blue)((-9))^2 - (4 * color(red)(4) * color(green)(0))))/(2 * color(red)(4))
x = (9 +- sqrt(81 - 0))/8
x = (9 +- sqrt(81))/8
x = (9 - 9)/8 and x = (9 + 9)/8
x = 0/8 and x = 18/8
x = 0 and x = 9/4